Analisis Buku Bahasa Arab Kemenag RI 2020 Untuk Kelas XI MA Dalam Perspektif Abdurrahman Ibrahim Al Fauzan - Nisa Fitriani; Triadi Wicaksono; Asep Maulana (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2022)
Purpose- This study aims to analyze Qiraah teaching materials in MA class XI Arabic books published by the Ministry of Religion of the Republic of Indonesia in 2020 in detail and comprehensively from the perspective of Abdurrahman Ibrahim Al Fauzan.  Design/Methodology/Approach- This study uses library research methods (library research). Where data collection techniques are carried out through a review of various books, literature, records, and reports related to the problem to be solved.  Findings- The results showed that good Qira'ah teaching materials have at least thirteen philosophical and technical criteria according to Abdurrahman Ibrahim Al Fauzan namely: comprehensive, integrated, synergistic, and simultaneous which means that teaching materials teach language along with its three components, namely: phonemes (ashwat), morpheme (mufradat), and structure (taraakiib) also cover the four language skills, namely: listening (istima’), speaking (kalam), reading (qira’ah), and writing (kitabah). The other criteria are gradual, using fushha Arabic, marked, without intermediary language, using Arabic and Islamic culture, direct discussion, varied reading texts, equipped with learning evaluations, making conversation as an introduction and learning axis, having qualified lay out, design, and appearance, supported by supporting supplements, and has been scientifically tested.  Research Limitation/Implications- This research is limited to MA class XI Arabic books published by the Ministry of Religion of the Republic of Indonesia in 2020. In addition, this research is still theoretical in nature without any field tests as a comparison instrument. However, this research can be the first step in the assessment and evaluation of these teaching materials, whether they are based on the scientific hypotheses of experienced Arabic learning experts or not.